Prevalence and factors associated with burnout in dental students of seven Cuban universities - Cossio-Alva, Bryan Alexis; Corrales-Reyes, Ibraín Enrique; Herrera-Plasencia, Paul Martín; Mejia, Christian R. (Frontiers in Education, 2025)
IntroductionThe burnout syndrome affects diverse populations and among them undergraduate students, which can weigh down their academic performance and professional future.ObjectiveThis study aims to determine the prevalence and factors associated with burnout syndrome among dental students from seven Cuban universities.MethodsMulticenter, observational, analytical and cross-sectional study developed in 7 Cuban universities. The validated version of the Maslach Burnout Inventory-Students Survey (MBI-SS) was used as a dependent variable. Prevalence ratios and 95% confidence intervals were calculated.ResultsA total of 738 students participated, of whom 470 (63.8%) were women. The average age was 21.7 ± 1.7 years. The prevalence of burnout was 34.8% (n = 257). In the multivariate model, it was found that having an academic advisor was associated with a high burnout score (RPa: 2.10; 95% CI: 1.18–3.74; p = 0.012). In contrast, having published a scientific article was associated with a lower score (RPa: 0.38; 95% CI: 0.23–0.64; p < 0.001).ConclusionOne third of the students presented burnout. Having an academic tutor and having made a scientific publication were the associated factors identified.